Draft Evidence by the Nursing Advisory Committee of the Trades Union Congress on nursing conditions & recruitment
1938-03-02 1938 1930s 9 pages - 6 - Interchangeability of Pensions. 23. On this matter representatives of Congress interviewed the Minister of Health whilst the recent Local Government Superannuation Act was passing through its Parliamentary stages, and urged him to extend the scope of the Act to allow for interchangeability between the schemes formed under the Local Government Superannuation Act and those under the Federated Hospitals Superannuation schemes. A memorandum on this matter has been drawn up for the information of the Minister of Health and active consultations are expected in the near future. This reform is particularly important to the Voluntary Hospitals because we visualise the continued growth of the Municipal Hospital Service which operates a common Superannuation Scheme. We believe that the greatest possible measure of Interchangeability will not only improve prospects of the nurses in Voluntary Hospitals, but will also be to the advantage of both Voluntary and Municipal Service. Living In. 24. We visualise the time when the majority of nurses attached to a hospital will "live out". It is a symptom of the spirt of the age that young persons demand a much greater measure of independence and freedom in their leisure time than their parents had. Hospitals will have to adapt themselves to this demand and provide for a large proportion of their staff to be entirely free from hospital regulations and discipline after an 8 hours period of duty each day. This may cost more, but on the other hand it will save considerable expenditure in the provision of nurses' homes, etc. Incidentally, this will probably popularise the nursing profession in those towns which contain a hospital recognised as a training school. Food. 25. We are of the opinion that in the majority of cases the food supplied to nurses is of good quality in its raw state, but it is spoiled by inefficient and unimaginative cooking. Constant and weary processions of rice puddings, excellent though that comestible may be, do not tempt the tired nurse, even with the addition of 3 or 4 half-stewed prunes. Persons who are subject to fatigue and nervous strain require nourishing and tasty food. 26. Again we have had complaints of the insufficient supply of food, and have been told that unless a nurse is quickly at the table she will find that someone else has taken the largest portion of her share of the meal. It is not much use lecturing nurses on the value of dietetics if they themselves have to hastily consume badly cooked food and the irony of this position has not been overlooked in many institutions. Status of Student Nurses. 27. In some quarters it is argued that Nursing is the only profession which trains the entrants free of cost and provides them board and lodging and pocket money in addition. We do not subscribe to this point of view. We consider that Student Nurses more than pay for their 292/54.73/2/18-22